1991
DOI: 10.1080/10825541.1991.11669988
|View full text |Cite
|
Sign up to set email alerts
|

The Motivational Responses of High, Average, and Low Achievers To Simple and Complex Language Arts Assignments: Classroom Implications

Abstract: Motivation to learn declines as students progress through elementary grades and drops precipitously as they enter middle school. A variety of reasons have been given for this decline from both developmental and environmental researchers. What has not been closely examined is the potential influence of different types of classroom assignments on the student motivation decline. In order to examine the decline, the influence of simple and complex language arts assignments on high, average, and low ability groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…In the present study, we extend findings from several earlier studies whose authors evaluated how various reading 286 JUDITH L. MEECE University of North Carolina at Chapel Hill and language arts assignments influence upper elementarygrade students' motivation (Hooper & Miller, 1991;Miller, Adkins, & Hooper, 1993;Miller & Meece, 1991. Their findings indicated that the students were more intrinsically motivated to complete assignments when they wrote multiple paragraphs over several days while collaborating with peers than when they simply underlined answers or wrote single words or phrases while working alone.…”
supporting
confidence: 63%
“…In the present study, we extend findings from several earlier studies whose authors evaluated how various reading 286 JUDITH L. MEECE University of North Carolina at Chapel Hill and language arts assignments influence upper elementarygrade students' motivation (Hooper & Miller, 1991;Miller, Adkins, & Hooper, 1993;Miller & Meece, 1991. Their findings indicated that the students were more intrinsically motivated to complete assignments when they wrote multiple paragraphs over several days while collaborating with peers than when they simply underlined answers or wrote single words or phrases while working alone.…”
supporting
confidence: 63%